On the Digital Ecosystem of the Modern University - Alexander Klimov; Evgeny Zarechkin; Vasily Kupriyanovsky (Современные информационные технологии и IT-образование, 2019)
The process of digital transformation is progressively englobing education, learning and management processes within the system of higher education. This trend at the level of universities has resulted in emergence, evolution and development of the concept of the “digital university” and of more advanced construct of university digital ecosystem. The article considers different aspects of the concept of university digital ecosystem, studying the results of implementation of digital learning and management technology into the practices of world and Russian universities, obstacles and outlook for their further extension, and risks accompanying digital transformation of universities. The article concludes that the process of forming and developing university digital ecosystems should consider complexity of factors accounting for diversified conditions, objectives, tasks and results of building a digital ecosystem. The main conclusion is that concept of digital transformation should be integrated into university development strategy.